Albright’s hereditary osteodystrophy in conjunction with growth hormone deficiency and adrenal insufficiency - (:unkn) unknown (My University, 2011)
Pseudohypoparathyroidism (PHP) is a rare disease presenting with hypocalcemia, hyperphosphataemia and increased secretion of PTH due to tissue unresponsiveness to the biologic actions of PTH. The term pseudo-pseudohypoparathyroidism (pPHP) is used for patients having the phenotype of Albright’s hereditary osteodystrophy (AHO) along with normal biochemical parameters.. The Gs alfa deficiency in PHP Ia may be associated with resistance to TSH or to gonadotropins, resulting in thyroidal and gonadal dysfunction. The female patient presented in this report had all the clinical features of AHO such as a round face, short stature, a short neck, obesity, short of 4th and 5thmetacarpals and 4thmetatarsal bones symmetrically. PTH level was high, while calcium and phosphorus levels were normal. Her major problem was hypertension resistant to treatment. She was severely obese, her family history for hypertension was strongly positive, but she also had metabolic syndrome. It was speculated that the hypertension was linked to the metabolic syndrome or was associated with the family history rather than be a component of PHP. The patient had both GH deficiency, confirmed by an insulin tolerance test, and adrenal insufficiency. To the best of our knowledge this is the first report of a case of PHP Ia or pPHP in conjunction with both GH and adrenal insufficiency.

Psödohipoparatiroidizm, dokularda PTH duyarsızlığı sonucu hipokalsemi, hiperfosfatemi ve hiperparatiroidi ile seyreden nadir bir hastalıktır. Klinik olarak Albright’ın herediter osteodistrofisi (AHO) fenotipine sahip ama biyokimyasal parametreleri normal olan hastalar ise psödo-psödohipoparatiroidi (pPHP) olarak isimlendirilir. PHP tip Ia’da Gs alfa eksikliği, gonadotropinlere ve TSH’ya direnç ile birlikte görülebilir. Bu yazıda bildirdiğimiz hastada AHO’nun tüm klinik bulguları mevcuttu. PTH düzeyleri yüksek, ancak kalsiyum ve fosfor düzeyleri normaldi. Hastanın esas yakınması tedaviye dirençli hipertansiyondu. Ailede de hipertansiyon öyküsü mevcuttu ve hasta ileri derecede obezdi. Sekonder hipertansiyon açısından yapılan incelemeler de negatif bulundu. Hastada GH eksikliği ve adrenal yetersizlik tespit edildi. Literatürde PHP tip Ia vakalarında gonadotropin, TSH ve GH direnci bildirilmiştir, ancak bu vakalarda ACTH veya kortizol direncine ilişkin yeterli veri bulunmamaktadır. Bu hastamızı, GH eksikliği ve adrenal yetersizlik ile birlikte olan, bir tip Ia PHP vakası olarak bildiriyoruz. Bilgilerimize göre bu, literatürde ilk vakadır.
Albright herediter osteodistrofisi ile birlikte büyüme hormonu eksikliği ve adrenal yetersizlik
Keywords: Endokrinoloji ve Metabolizma